Investigation of deuterium retention in/desorption from beryllium-containing mixed layers. (January 2016) - Sugiyama, K.; Porosnicu, C.; Jacob, W.; Jepu, I.; Lungu, C.P.
Highlights: Deuterium retention and release characteristics of beryllium-containing mixed material layers were investigated towards an assessment of the efficiency of the tritium removal procedure currently suggested for ITER. Retention and the removal efficiency by ITER baking procedure will strongly depend on the composition of the deposited layer and the wall temperature during plasma operation. Abstract: This article reports experimental results regarding the deuterium (D) retention and release characteristics of beryllium-containing mixed material layers. The main aim is an assessment of the efficiency of the tritium removal procedure currently suggested for ITER, i.e., wall baking at 513 K (240 °C) for the main chamber walls and 623 K (350 °C) for the divertor. It is observed that the tritium retention as well as the removal efficiency by a following baking procedure will strongly depend on the composition of the deposited layer and the wall temperature during plasma operation. In the case that D is implanted at moderate temperatures (300 to 400 K), which would correspond to the "cool divertor" scenario in ITER, a large fraction of retained D is trapped in states having a low D binding energy and correspondingly low release temperature. Therefore, in this case baking can release a significant amount of retained D. On the other hand, if D is implanted at temperatures above 520 K, which would correspond to the "hot divertor" scenario in ITER, the amount of retained D will be significantly lower, but the retained D is predominantly trapped in high-energy binding states. In such a case, even baking at 623  K might not efficiently remove the retained tritium.